Evaluation of a hydrothermal process for pretreatment of wheat straw : effect of particle size and process conditions - Ruiz, Héctor A. (2011)
Hydrothermal processes are an eco-friendly processes that provide an interesting alternative for chemical utilization of lignocellulosic materials, in which water and crop residues are the only reagents. In this work the effect of process conditions (size distribution of the wheat straw, temperature and time) was evaluated against production of fermentable products. RESULTS: The use of milled wheat straw fractions as a raw material containing blends of different particle size distribution showed that the latter had an influence on the final sugars in the hydrolysate. Improved values of glucose (21.1%) and xylose yields (49.32%) present in the hydrolysate were obtained with treatment severity factors of 2.77 and 3.36, respectively. Mathematical models were developed aimed at establishing the effect of process conditions on monosaccharide concentration and its degradation in the liquor. CONCLUSION: This work shows that the use of wheat straw blends with various particle sizes has a significant effect on the extraction of fermentable products. The effect of treatment severity, which takes into account both processing time and temperature was also evaluated. These results are of importance for process design.